Interdiffusion in critical binary mixtures by molecular dynamics simulation - Binder, Kurt; Das, Subir K.; Fisher, Michael E.; Horbach, Jürgen; Sengers, Jan V. (Diffusion Fundamentals, 2007)
A simulation study of the static and dynamic critical behavior of a symmetric binary Lennard-Jones mixture is briefly reviewed. Using a combination of semi-grand-canonical Monte Carlo (SGMC) and molecular dynamics (MD) methods near the critical temperature of liquid-liquid unmixing, the correlation length and “susceptibility” related to the critical concentration fluctuations are estimated, as well as the self- and interdiffusion coefficients. While the self-diffusion coefficient does not show a detectable critical anomaly, the interdiffusion coefficient is found to vanish when one approaches the critical temperature at fixed critical concentration. It is shown that in the corresponding Onsager coefficient both a divergent singular part and a nonsingular background term need to be taken into account. With appropriate finite-size scaling analysis (the particle numbers studied for the dynamics lie only in the range from N = 400 to 6400), the critical behavior of the interdiffusion coefficient is found to be compatible both with the theoretically predicted behavior and with corresponding experimental evidence.